Pemetaan Strategi Komunikasi Pergerakan Feminis Indonesia di Ruang Digital - Wijdan, Syifa; Siscawati, Mia; Wijdan, Syifa Maulida; Santoso, Widjajanti (Jurnal Pekommas, 2024)
This research aims to explore the communication strategies of the digital feminist movement in Indonesia in using social media as a space for message propagation. In the digital era, social media has become the main instrument for feminist communities to deconstruct common gender narratives and advocate for issues related to gender equality and women's empowerment. Using the Systematic Literature Review (SLR) approach, this research analyzes several relevant literatures to identify the communication strategies applied by Indonesian feminist communities. The results show that these communication strategies include decentralization of information, increased interactivity with audiences, utilization of social media-specific features such as hashtags and highlights, and the use of multimedia content to increase audience appeal. The findings highlight how social media is becoming an influential tool that enables inclusive and collaborative advocacy in the digital space, with challenges of limited internet access and intergenerational differences in understanding how to operate social media features